PERAIRAN BERMASALAH : TANTANGAN MARITIM DI ASIA PASIFIK - Marsetio, Marsetio (Jurnal Pertahanan dan Bela Negara, 2018)
Asia Pacific is a region with great attractions and also highly dynamic, with its growth and economic pulse that affects economy of the world. High economic growth coupled with regionalism and globalization generates implications the emergence of issues related to maritime security, national borders, disputes on territory rich in resources, environmental issues, transnational organized crimes, natural disasters, and energy and food security. Globalization itself creates new interactions among regional countries as a precondition to solve and face common problems in maritime domain awareness network. Regional Maritime Partnership is a smart choice when regional stability is becoming the goal of all states to maintain regional resilience. Indonesiaâ€™s position is unique as the link between two regions (Pacific and Indian Ocean) dependent on each other. Indonesia never recedes in providing the drive for regional stability through balancing strategies without becoming entangled in alliances. Indonesian Navy as a component of national strength participates in the application of national strategy into naval strategy and operationalizing it in diplomacy and multilateral exercises to enhance interoperability among navies in Asia Pacific, especially among ASEAN nations. Â Keywords: Maritime Challenges, Maritime Security, Maritime Domain Awareness (MDA), Regional Maritime Partnership.